PENTINGNYA PENGUASAAN METODE PENELITIAN BAGI GURU [THE IMPORTANCE OF MASTERING RESEARCH METHOD FOR TEACHERS] - Niko Sudibjo; Juanna Judith Huliselan; Innocentius Bernarto (Universitas Pelita Harapan, 2020)
The research method is the most essential element in conducting scientific research. Teachers need to master scientific research methods as a prerequisite for writing scientific papers, which are part of improving teachers' quality and professionalism. In addition, scientific research and publications are requirements for applications for promotion of functional ranks and government teacher certification. The aim of this workshop is to help teachers understand quantitative and qualitative research methods. The workshop is carried out through class discussions with the participants. The speaker first presented the material, then continued with a simple guided exercise in the class discussion. The data from the workshop were collected by means of tests to see the participants' understanding of the material and a questionnaire to see the usefulness of the workshop given. Based on the survey results, it was found that this research method workshop was well understood and beneficial to teachers.BAHASA INDONESIA ABSTRACT: Metode penelitian menjadi elemen yang sangat penting dalam membuat penelitian ilmiah. Para guru perlu menguasi metode penelitian ilmiah sebagai bekal menulis karya ilmiah yang termasuk salah satu upaya peningkatan kualitas profesionalisme guru. Lebih lagi, penelitian ilmiah dan publikasi merupakan syarat pengajuan kenaikan jabatan fungsional guru serta sertifikasi. Tujuan dari workshop ini adalah untuk membantu para guru untuk memiliki pengetahuan mengenai metode penelitian kuantitatif dan kualitatif. Workshop dilakukan melalui diskusi kelas dengan peserta. Pembicara terlebih dahulu mempresentasikan materi, kemudian dilanjutkan dengan latihan terbimbing sederhana dalam diskusi kelas. Data hasil workshop dikumpulkan melalui tes untuk melihat pemahaman peserta terhadap materi dan angket untuk melihat kegunaan workshop yang diberikan. Berdasarkan survey angket, diketahui bahwa workshop metode penelitian ini dapat dipahami dengan baik dianggap bermanfaat bagi para guru.